Pengaruh Motivasi Eksternal terhadap Peningkatan Kinerja Karyawan di PT. Radio Bali Suara Mitra Dewata - Tegar Cipta Taurival (Majalah Ilmiah Widyacakra, 2019)
The research was conducted at PT. Radio Bali Suara Mitra Dewata. The purpose of the research is to determine the effect of external motivation on improving employee performance. The study was conducted by distributing questionnaires to 25 employees. Data analysis used included, validity test, reliability test, normality test, heteroscedasticity test, simple linear regression test and t test. Based on the results of the validity test there are 5 invalid questions and 30 valid questions. The invalid instrument is deleted because it is an outlier data. Based on the results of the reliability test showing external motivation has cronbach alpha of 0.859 while Cronbach alpha on employee performance is 0.888. This shows that the instrument used is reliable. From the results of the normality test the value of Asymp Sig is 0.200 which means greater than 5% (0.05). This shows that the data used in this study is normally distributed. For the results of heteroscedasticity test, it was found that sig. independent variable 0.279 more than 0.05. It can be said that this shows no heteroscedasticity. From the results of a simple liner regression test shows a = 49,719 means that if there is no increase in external motivational coefficients, then the constant value of employee performance is 49,719, then b = 0,271 means that if there is an increase in external motivation coefficient of one unit, then the constant value of employee performance is 0.271. While the results of the t test show that the value of t count = 1.305 <t table 2.068, so that H0 is accepted and H1 is rejected. It can be concluded that in the study there was no relationship between the effect of giving external motivation on improving employee performance at PT. Radio Bali Suara Mitra Dewata.